Common mental disorders in pregnancy and postnatal depressive symptoms in the MINA-Brazil study: occurrence and associated factors - Bruno Pereira da Silva; Alicia Matijasevich; Maíra Barreto Malta; Paulo A R Neves; Maria Cristina Mazzaia; Maria Cristina Gabrielloni; Márcia C Castro; Marly Augusto Cardoso (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To investigate the occurrence and factors associated with common mental disorders in pregnancy and depressive symptoms in postpartum, as well as the association between both in the Brazilian Western Amazon. METHODS This is a prospective cohort in the MINA-Brazil study with women who received primary health care in the town of Cruzeiro do Sul, Acre State. We performed two clinical evaluations during pregnancy (the first: 16-20 weeks; the second: 28 gestational weeks) and three postpartum evaluations (at 3, 6 and 12 months), in which demographic and socioeconomic, gestational, lifestyle and clinical data were collected. We used the Self-Reported Questionnaire (score ≥ 8) to screen the gestational common mental disorder and the Edinburgh Postnatal Depression Scale (score ≥ 10) to identify postpartum depressive symptoms. We used adjusted ordinal logistic regression to investigate the relationship between the covariates and the occurrence of common mental disorders in pregnancy and postpartum depressive symptomatology. RESULTS A total of 461 women completed the two clinical evaluations in pregnancy; of these, 247 completed the three postpartum evaluations. The occurrence of common mental disorder during pregnancy was 36.2% and 24.5% in the first and second evaluations, respectively, and the cumulative incidence was 9.2%. In addition, 50.3% maintained the disorder between evaluations. During postpartum, approximately 20% of the mothers presented depressive symptoms during the first year of their children's lives. Parity (≥ 2) was associated with common mental disorders, while low maternal education was associated with postpartum depressive symptoms. Women with a common mental disorder in both evaluations during pregnancy were 5.6 times more likely (95%CI: 2.50-12.60) to develop postpartum depressive symptoms. CONCLUSION The occurrence of common mental disorder at any time assessed during pregnancy, but especially its persistence from the second trimester, was strongly associated with depressive symptoms after childbirth. These findings highlight the need for early screening and monitoring of the mental health of pregnant women at the start of prenatal care in order to reduce possible negative impacts on the health of the mother-child binomial caused by such events.